1984
DOI: 10.1159/000149509
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Measles Virus Antigens in Acutely and Persistently Infected Cells Using Monoclonal Antibodies: Differences in the Accumulation of Certain Viral Proteins

Abstract: Monoclonal antibodies were used to study measles virus (Hallé strain) infections. The distribution of virus antigens in acutely and persistently infected cells was examined by immunofluorescence, and the synthesis of the virus polypeptides in acutely infected cells was measured after immunoprecipitation and analysis in SDS-polyacrylamide gels. The virus nucleoprotein (NP) was detected 12 h after infection and was the major virus polypeptide synthesized throughout the virus cycle. The NP, matrix, and polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…It is interesting that the intracellular distribution of measles antigens in the osteoclasts (Fig. l) is more consistent with the pattern found in persistently infected tissue culture cells (Giraudon et aL, 1984, Norrby et al, 1982. Thus the measles NP antigens could be detected in both nuclei and cytoplasm and indeed agree with ultrastructural studies which show that both the cytoplasm and nuclei of Pagetic osteoclasts contain microcylindrical structures very similar in dimensions and nature to paramyxovirus nucleocapsids (Rebel et aL, 1980a, b).…”
Section: Discussionsupporting
confidence: 84%
“…It is interesting that the intracellular distribution of measles antigens in the osteoclasts (Fig. l) is more consistent with the pattern found in persistently infected tissue culture cells (Giraudon et aL, 1984, Norrby et al, 1982. Thus the measles NP antigens could be detected in both nuclei and cytoplasm and indeed agree with ultrastructural studies which show that both the cytoplasm and nuclei of Pagetic osteoclasts contain microcylindrical structures very similar in dimensions and nature to paramyxovirus nucleocapsids (Rebel et aL, 1980a, b).…”
Section: Discussionsupporting
confidence: 84%
“…Monoclonal antibodies have proven to be powerful tools in the study of measles virus, having revealed subtle antigenic difference and variability of measles virus proteins previously considered to be invariable (Birrer et al, 1981a, b;Giraudon & Wild, 1981;Trudgett et al, 1981;ter Meulen et al, 1981 ;Sheshberadaran et al, 1983), the presence of multiple antigenic sites within some structural proteins (Carter et al, 1982(Carter et al, , 1983a and localization of various viral antigens in productive and non-productive infections (Norrby et al, t982;Johnson et aL, 1982;Giraudon et al, 1984). We have also attempted to prepare monoclonal antibodies against structural proteins of measles virus.…”
Section: Introductionmentioning
confidence: 99%
“…Neither labelling with monospecific antibodies nor with the polyvalent antiserum gave evidence for a random or diffuse distribution of polypeptides as noticed in immunofluorescence and pre-embedding labelling studies [11,17]. The label was largely confined to inclusions and plasma membrane bound virus structures, suggesting that these polypeptides do not enter a pool, but assemble rapidly after synthesis.…”
Section: Discussionmentioning
confidence: 84%